India-Thailand Cultural Interactions : Glimpses from the Past to Present - Ghosh, Lipi (Springer Singapore : Imprint: Springer, 2017)
This volume looks at facets of cultural interactions between India and Thailand-two historically significant countries of the South East Asian region. For the first time a comprehensive discussion on historical and contemporary cultural interactions between Indian and Thailand has been attempted in this volume. Asianization has become an important contemporary concept and, in this context, understanding cultural exchange within Asia is an important exercise. The chapters in this volume include contributions from noted scholars based in India and Thailand on different areas of cultural exchange: from religion, to art, artefacts, clothing, music-especially Indian classical music, cuisine, and the contemporary use of shared civilizational tools in the cultural diplomacy of both countries. Written in a lucid and accessible language, the chapters in this insightful volume are of interest to academics and researchers of cultural studies, Asian studies, development studies, modern Asian history, policy makers and general readers.